VIRAL HEPATITIS: DIFFERENCES AMONG TYPES A, B, AND C AND PREVENTION STRATEGIES - Safarova Dilora Rustam qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Viral hepatitis, an inflammation of the liver caused by hepatitis viruses, remains a major global public health concern. Among the different types, hepatitis A, B, and C are the most prevalent and differ significantly in their transmission modes, clinical outcomes, and preventive measures. This article provides a comparative overview of hepatitis A, B, and C, focusing on their epidemiology, symptoms, diagnostic approaches, and prevention strategies. Emphasis is placed on vaccination, hygiene, and safe medical practices as key components of control and elimination efforts.